Seeking Asylum: Factors Driving Irregular Migration from Indonesia to Australia during the Fifth Wave 2008–2013. (24th December 2018) - Clark, Sally
Abstract: This article explores factors driving irregular migration from Indonesia to Australia from 2008–2013. During this time Australia witnessed an increase in the number of onshore asylum-seekers arriving from Indonesia with the assistance of people smugglers. In Australia this phenomenon was seen as a consequence of the Government's dismantling of hard-line border security policies implemented by its predecessor. However, this framing obfuscated the fact that most industrialised countries witnessed a similar increase in the number of asylum applications during this period, suggesting a more complex analysis of irregular migration is needed. With the aim of understanding the factors that influenced people's migration decisions during this time, 30 asylum-seekers who were either in transit in Indonesia during this period, or had previously transited through Indonesia before making irregular boat voyages to Australia were interviewed. Through these personal accounts a greater understanding of the factors driving irregular migration can be gained. This research found that people were extremely reluctant to move irregularly across borders and were committed to being resettled through "proper channels". Yet fundamental flaws in the refugee status determination process in Indonesia, coupled with a lack of physical safety, severe material deprivation and social isolation all challenged their resolve.